Blogging for ESL learners : a case study / Nidana Yahya - Yahya, Nidana (2011)
This paper reports on a study designed to investigate and identify (a) the advantages of blogging (b) students' view on blogging. Moreover, this study is also to seek (c) teachers' view on blogging activity and (d) the limitations and drawbacks from blogging. Participants were 31 English second language learners of a English as Second Language Studies class and 5 English teachers. Data included response to a questionnaire and interview questions. Analyses and comparison of the students' and teachers' responses show that blogging offers them a lot of advantages and benefits that helps to improve their performance in writing tasks. However, there are some drawbacks and limitations addressed in this study prior to weblogs. The results of the study are interpreted with an understanding of its limitations, and directions for further research are also discussed.